A Multiplex PCR Detection Assay for the Identification of Clinically Relevant Anaplasma Species in Field Blood Samples - Peng, Yongshuai; Zhao, Shanshan; Wang, Kunlun; Song, Jinxing; Yan, Yaqun; Zhou, Yongchun; Shi, Ke; Jian, Fuchun; Wang, Rongjun; Zhang, Longxian; Ning, Changshen (Frontiers in Microbiology, 2020)
The genus Anaplasma (Rickettsiales: Anaplasmataceae), which includes the species A. capra, A. bovis, A. ovis and A. phagocytophilum, is responsible for a wide variety of infections in both human and veterinary health worldwide. Multiple infections with these four Anaplasma pathogens have been reported in many cases. We introduce a novel multiplex PCR for the simultaneous detection of A. capra, A. bovis, A. ovis and A. phagocytophilum, based on species-specific primers against the groEL (A. capra and A. bovis), msp4 (A. ovis) and 16S rRNA (A. phagocytophilum) genes. To verify the specificity of the PCR reactions, we evaluated four sets of primers to analyze samples containing different blood pathogens. The sensitivity of the multiplex PCR was evaluated by amplifying 10-fold dilutions of total genomic DNA extracted from sheep blood infected with A. capra, A. bovis, A. ovis or A. phagocytophilum. The reproducibility of the assay was evaluated by testing 10-fold dilutions of total genomic DNA extracted from sheep blood infected with these pathogens from 100–10-3 ng/µL per reaction in triplicate on three different days. A total of 175 field blood DNA samples were used to evaluate the reproducibility of multiplex PCR compared with the simplex PCRs. PCR primers used in this study were confirmed to be 100% species-specific using blood pathogens previously identified by other methods. The lower limit of detection of the multiplex PCR with good repeatability enabled the detection of A. capra, A. bovis, A. ovis and A. phagocytophilum at concentrations of 3×10−5, 5×10−7, 2×10−5, and 7×10−7 ng/µL, respectively. There was no significant difference between conventional and multiplex PCR protocols used to detect the four Anaplasma species (P > 0.05). The results of the multiplex PCR revealed that the A. capra groEL gene, the A. bovis groEL gene, the A. ovis msp4 gene and the A. phagocytophilum 16S rRNA gene were reliable target genes for species identification in clinical isolates, being specific for each of the four target Anaplasma species. Our study provides an effective, sensitive, specific and accurate tool for the rapid differential clinical diagnosis and epidemiological surveillance of Anaplasma pathogens in sheep and goats.